2004
DOI: 10.1089/sur.2004.5.309
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Myositis and Vasculitis: An Unusual Necrotizing Soft Tissue Infection

Abstract: Cryptococcal soft tissue infection serves as a marker of disseminated cryptococcosis in immunocompromised hosts. Owing to its rarity as a cause of soft tissue infections, diagnosis is difficult and mortality is high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Cryptococcus neoformans infection may rarely present with infectious myositis (78,87,210). Most infections with this organism are asymptomatic; however, after the inhalation of the fungus, pulmonary, skin, or central nervous system (CNS) disease may occur.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
See 2 more Smart Citations
“…Cryptococcus neoformans infection may rarely present with infectious myositis (78,87,210). Most infections with this organism are asymptomatic; however, after the inhalation of the fungus, pulmonary, skin, or central nervous system (CNS) disease may occur.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
“…Most cases occur among immunosuppressed persons; a review of the literature showed that cases have occurred in transplant recipients and patients with leukemia/lymphoma, AIDS, and hepatitis C viral infection (17,78,87,102,116,165,210). Patients often present with lower extremity pain and swelling.…”
Section: Cryptococcus Neoformansmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryptococcal soft-tissue infection serves as a marker of disseminated cryptococcosis [13]. In our case, cryptococcal myositis developed in a patient with DM, and disseminated pulmonary infiltration was proven pathologically.…”
Section: Discussionmentioning
confidence: 56%
“…32 Despite treatment with anti-fungal therapy, the clinical course may be deleterious with evolution to necrotizing fasciitis. Surgical debridement may be necessary, 33 although it may lead to systemic involvement, as suggested in the present patient report. Overall mortality of cryptococcal cellulitis is high.…”
Section: Discussionmentioning
confidence: 78%